2012
DOI: 10.1164/rccm.201111-2017oc
|View full text |Cite
|
Sign up to set email alerts
|

Galactose-α-1,3-Galactose–Specific IgE Is Associated with Anaphylaxis but Not Asthma

Abstract: These results provide a model of an ectoparasite-induced specific IgE response that can increase total serum IgE without creating a risk for asthma, and further evidence that the main allergens that are causally related to asthma are those that are inhaled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
84
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 44 publications
1
84
1
1
Order By: Relevance
“…The 3 patients with IgE against α-Gal all ate red meat without having any acute or delayed symptoms. Commins et al [9] have reported that α-Gal titres among anaphylaxis-urticaria patients with red meat allergy make up at least 10% (or 30%) of total serum IgE. Upon investigating the fraction of α-Gal IgE to total IgE among our 3 patients, we found that it was less than 2%, supporting that the low titres we observed are not related to red meat allergy.…”
Section: Discussionsupporting
confidence: 80%
“…The 3 patients with IgE against α-Gal all ate red meat without having any acute or delayed symptoms. Commins et al [9] have reported that α-Gal titres among anaphylaxis-urticaria patients with red meat allergy make up at least 10% (or 30%) of total serum IgE. Upon investigating the fraction of α-Gal IgE to total IgE among our 3 patients, we found that it was less than 2%, supporting that the low titres we observed are not related to red meat allergy.…”
Section: Discussionsupporting
confidence: 80%
“…27 For example, cetuximab can generate an anaphylactic response due to its heterogeneous glycan forms, such as a-1,3 galactose and hydroxyacetylneuraminic acid (NGNA). 28 In our study of CTLA4-Ig glycosylation, we analyzed the biosimilar candidate using 3 different approaches: (1) intact protein level glycan analysis, (2) peptide level glycan analysis, and (3) cleaved glycan level analysis.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, they have used antibodies against alpha-gal in human sera to stain the cryostat preparations of the tick which is thought to induce these responses in Stockholm [15 ▪▪ ]. The area of Sweden where we have screened sera from school children is almost 800 miles north of Stockholm and less than 1% of those sera tested positive for IgE to alpha-gal [30,31 ▪ ]. Interestingly, there are no ticks in that area.…”
Section: Late-onset and Delayed Reactions To Mammalian Food Products mentioning
confidence: 99%